Asymmetric thermally activated delayed fluorescence (TADF) emitters with 5, 9-dioxa-13b-boranaphtho[3, 2, 1-de]anthracene (OBA) as the acceptor and highly efficient blue-emitting OLEDs. Issue 38 (18th September 2019) - Song, Dongdong; Yu, Yue; Yue, Ling; Zhong, Daokun; Zhang, Yindi; Yang, Xiaolong; Sun, Yuanhui; Zhou, Guijiang; Wu, Zhaoxin
Abstract : With 5, 9-dioxa-13 b -boranaphtho[3, 2, 1- de ]anthracene (OBA ) as the acceptor, thermally activated delayed fluorescence (TADF) emitters adopting an asymmetric configuration can achieve highly efficient blue-emitting OLEDs. Abstract : A series of new organic emitters was prepared by introducing various donors (Ds) to the meta -position of the boron atom in the central phenyl ring in the acceptor (A) of 5, 9-dioxa-13 b -boranaphtho[3, 2, 1- de ]anthracene (OBA ). Moreover, their thermal, photophysical, electrochemical and electroluminescent (EL) properties were characterized in detail. The photophysical results revealed that these OBA -based molecules adopted a D–A configuration and exhibited efficient thermally activated delayed fluorescence (TADF) properties with a reverse inter-system crossing constant ( k RISC ) in the order of 10 5 s −1 . It has been shown that introducing the –Br group to the OBA acceptor could increase k RISC by 2 to 3 times. Importantly, the deep-blue TADF emitter OBA-O showed a high photoluminescent quantum yield (PLQY) of 0.84, while its blue analog OBA-BrO with the –Br group exhibited an even higher PLQY of 0.92 in the doped film state. Benefitting from their high PLQYs as blue-emitting TADF emitters, the doped organic light-emitting diodes (OLEDs) based on these OBA -based TADF emitters exhibited attractive electroluminescent (EL) performances. The blue-emitting OLEDs with CIE (0.17, 0.17) showed the maximum external quantum efficiency ( η ext ) of 17.8%, current efficiency ( η L ) of 33.2 cd A −1 and power efficiency ( η P ) of 34.2 lm W −1, while that for the bluish-green device were 22.5%, 49.2 cd A −1 and 56.9 lm W −1, respectively. Thus, the great potential of these TADF emitter-based OBA acceptors was clearly demonstrated by their EL data. In addition, these asymmetric OBA -based molecules will enrich the structural diversity of this type of TADF emitter.